Factors associated with pharmacological and psychotherapy treatments adherence in patients with borderline personality disorder - Mirhaj Mohammadabadi, Motahareh Sadat; Mohammadsadeghi, Homa; Eftekhar Adrebili, Mehrdad; Partovi Kolour, Zahra; Kashaninasab, Fatemeh; Rashedi, Vahid; Shalbafan, Mohammadreza (Frontiers in Psychiatry, 2022)
Background: Borderline personality disorder is a major mental illness characterized by sustained relationship instability, impulsive behavior, and intense affects. Adherence is a complex behavior, from minor refusals to abandonment of treatment, which can be affected by various factors. Therefore, the present study aimed to investigate the factors affecting pharmacological and psychotherapy adherence, patients’ attitude towards medication, and assessing medication and treatment adherence in patients with borderline personality disorder referred to an outpatient referral clinic in Tehran, Iran. Methods: The study was a cross-sectional study. The files of patients with borderline personality disorder referred to the outpatient clinic of the Tehran Psychiatric Institute were reviewed as the first step. Data were collected using the Drug Attitude Inventory-10 (DAI-10) questionnaire and a questionnaire to determine the attitude of patients toward pharmacological and psychotherapy treatment as well as therapeutic adherence. After collecting data, patients’ therapeutic adherence was divided into poor, partial, and good compliance. Results: Ninety-four patients were involved in the study, and fifty-four were women. Findings of DAI showed that 54 (57.4%) participants had negative attitudes toward medication, while 38 (40.4%) participants showed a negative attitude toward psychotherapy treatment. Additionally, the percentage of patients with good psychotherapy adherence (44.7%) was higher than that of patients with good medication adherence (31.9%). The most common reasons for discontinuation of treatment were medication side effects (53.1%), dissatisfaction with the therapist (40.3%), and then fear of medication dependence (40%). Patients with higher education levels and a positive history of hospitalization in a psychiatric ward had better adherence to psychotherapy (P<0.05). Conclusions: Results of the current study show that attitude toward psychotherapy is more favorable than pharmacotherapy among patients with BPD. The rationale may be that medications are mainly prescribed for comorbid conditions and do not have substantial effects on the BPD symptoms, resulting in low medication adherence.